Characterization of Indian isolates of Fusarium oxysporum f. sp. cucumerinum using vegetative compatibility groups and RAPD assay - NAJAFINIA, MOUSA; SHARMA, PRATIBHA (Indian Phytopathology, 2011)
Fifty isolates of Fusarium oxysporum f. sp. cucumerinum, the causal agent of wilt of cucumber (Cucumis sativus) were obtained from infected tissues of cucumber seedlings, mature plants from different states in India, and studied by vegetative compatibility and random amplified polymorphic DNA (RAPD) assays. These isolates were grouped into vegetative compatibility groups (VCGs) by complementation tests using nitrate non utilizing (nit) mutants. All isolates were grouped into eight VCGs, which were named 1-A, 1-B, 1-C, 1-D, 1-E, 1-F, 1-G and 1-H. The first five groups were pathogenic isolates and the last three groups comprised non- pathogenic (to cucumber) ones. No self-incompatibility was observed in any of the isolates tested. Pathogenic and non-pathogenic isolates were not found in the same VCGs. RAPD markers detected high levels of polymorphism among the pathogenic isolates. Cluster analysis of the similarity index data classified the pathogenic isolates into four major groups, suggesting the existence of at least four pathogenic groups of the pathogen in the cucumber growing areas of India. Highest variation was seen among the pathogen isolates collected from Delhi and West Bengal followed by that in other states. Non-pathogenic isolates could be distinguished from pathogenic isolates. No correlation was found between RAPD data and geographic origin of the isolates.